2003
DOI: 10.1159/000072138
|View full text |Cite
|
Sign up to set email alerts
|

Th2- and to a Lesser Extent Th1-Type Cytokines Upregulate the Production of both CXC (IL-8 and Gro-Alpha) and CC (RANTES, Eotaxin, Eotaxin-2, MCP-3 and MCP-4) Chemokines in Human Airway Epithelial Cells

Abstract: Background: Both CXC and CC chemokines play an important role in leukocyte recruitment. However, a systematic examination of their production by human airway epithelial cells (HAECs) has not been carried out. The objective of this study was to investigate whether Th1- and Th2-type cytokines regulate chemokine production in HAECs. Methods: HAECs were grown from both nasal and bronchial tissue and subsequently stimulated with either Th1- or Th2-type cytokines. Results: Constitutive mRNA expression for gro-alpha,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…Our present results show that bronchial epithelial cells were the major source for the release of IL-6, CXCL8 and b-defensin2 in co-culture upon MDP stimulation. For innate immunity against microbial infection, activated bronchial epithelial cells are potent sources of a wide variety of proinflammatory cytokines and chemokines, such as CXCL8 [44,45]. Apart from MDP, Gram-negative bacterial cell wall component lipopolysaccharide and human rhinovirus can also activate epithelial cells to release anti-bacterial peptide b-defensin 2 [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Our present results show that bronchial epithelial cells were the major source for the release of IL-6, CXCL8 and b-defensin2 in co-culture upon MDP stimulation. For innate immunity against microbial infection, activated bronchial epithelial cells are potent sources of a wide variety of proinflammatory cytokines and chemokines, such as CXCL8 [44,45]. Apart from MDP, Gram-negative bacterial cell wall component lipopolysaccharide and human rhinovirus can also activate epithelial cells to release anti-bacterial peptide b-defensin 2 [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-4 has been reported to induce a delay of neutrophil apoptosis (36), suggesting that IL-4 by itself could play a role in the reduction of neutrophilic apoptosis observed in the lung and leading to neutrophil accumulation in the BALF. In addition, IL-4 is a multifunctional cytokine that can regulate the secretion of neutrophil-attracting chemokines such as growth-related oncogene-␣ and IL-8 (37), and control the expression of VCAM-1 on the surface of vascular endothelial cells (38), thereby modulating neutrophil recruitment and trafficking. In the present study, increased IL-4 levels are linked with anti-OVA-specific IgE levels that were strongly enhanced in the serum of MMP-8 Ϫ/Ϫ .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wang et al (19) identified IL-12 as a potential inducer of VCAM-1 expression. Also, IFN-␥ has been shown to induce expression of the named chemokines (31)(32)(33). One might speculate that, during the repeated airway challenges, IL-12 contributes directly or through an IFN-␥-dependent mechanism to enhanced expression of Th2 cytokines, eosinophil-recruiting chemokines, and VCAM-1.…”
Section: Cd3mentioning
confidence: 99%